Novel FOXG1 mutations associated with the congenital variant of Rett syndrome. Issue 1 (2nd July 2009) - Mencarelli, M A; Spanhol-Rosseto, A; Artuso, R; Rondinella, D; De Filippis, R; Bahi-Buisson, N; Nectoux, J; Rubinsztajn, R; Bienvenu, T; Moncla, A; Chabrol, B; Villard, L; et al.
Abstract : Background: Rett syndrome is a severe neurodevelopmental disorder representing one of the most common genetic causes of mental retardation in girls. The classic form is caused by MECP2 mutations. In two patients affected by the congenital variant of Rett we have recently identified mutations in the FOXG1 gene encoding a brain specific transcriptional repressor, essential for early development of the telencephalon. Methods: 60 MECP2/CDKL5 mutation negative European Rett patients (classic and variants), 43 patients with encephalopathy with early onset seizures, and four atypical Rett patients were analysed for mutations in FOXG1 . Results and conclusions: Mutations have been identified in four patients, independently classified as congenital Rett variants from France, Spain and Latvia. Clinical data have been compared with the two previously reported patients with mutations in FOXG1 . In all cases hypotonia, irresponsiveness and irritability were present in the neonatal period. At birth, head circumference was normal while a deceleration of growth was recognised soon afterwards, leading to severe microcephaly. Motor development was severely impaired and voluntary hand use was absent. In contrast with classic Rett, patients showed poor eye contact. Typical stereotypic hand movements with hand washing and hand mouthing activities were present continuously. Some patients showed abnormal movements of the tongue and jerky movements of the limbs. Brain magnetic resonance imaging showed corpus callosum hypoplasia in most cases, while epilepsy was a variable sign. Scoliosis was present and severe in the older patients. Neurovegetative symptoms typical of Rett were frequently present.